Programming Languages and Systems 24th European Symposium on Programming, ESOP 2015, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2015, London, UK, April 11-18, 2015, Proceedings - Vitek, Jan (Theoretical Computer Science and General Issues, 2015)
This book constitutes the proceedings of the 24th European Symposium on Programming, ESOP 2015, which took place in London, UK, in April 2015, held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2015. The 33 papers presented in this volume were carefully reviewed and selected from 113 submissions.